RESPON TANAMAN SAWI DI TANAH GAMBUT DENGAN PEMBERIAN ABU CANGKANG KERANG - Mita Setyowati; Iwandikasyah Putra; Banta Saidi (Universitas Teuku Umar, 2018)
The use of shells ash as an ameliorant could raise the pH, reduce degradation of nutrients and can supply nutrients in the peat soil. The shells ash were composed of calcium carbonate (CaCO3), which amounted to 53.05% CaCO3, Na at 0.08%, P 0.05%, 0.05% Mg, Fe 0.02%, Cu 16.36% , 15.76% Zn and 0.1% Si. This study aims to determine the response of mustad plants in peatlands with granting of shell clams ash. This research was conducted at the Experimental Farm Faculty of Agriculture, University of Teuku Umar, Meulaboh, Aceh Barat in April to June 2016. The research design used was a randomized block design (RAK)3 x 5 factorial design with three replications, ie varieties factor with 3 levels (V1 = Tosakan, V2 = Dora and V3 = Takana 801 and dose shells with 5 levels (D0 = 0 ton ha-1, D1 = 2 ton ha-1, D2 = 4 t ha-1, D3 = 6 ton ha-1 and D4 = 8 ton ha-1). There is no interaction between the dose of shells ash and varieties of all the observed variables, but the best dose of shellsash was 2 ton ha-1 and the best varieties was Tosakan. Keywords: ameliorant, mustard varieties, peats soils, shells